Spatial Patterns and Characteristics of Urban–Rural Agricultural Landscapes: A Case Study of Bengaluru, India - Jayan Wijesingha; Thomas Astor; Sunil Nautiyal; Michael Wachendorf (Land)
Globally, the agricultural landscape is the most exposed due to urbanisation. Therefore, finding the spatial and temporal patterns of changes in agricultural landscapes is essential for sustainable development. This study developed a workflow to address this information gap and determine the spatial patterns and characteristics of agricultural landscapes along an urban–rural gradient. The workflow comprised three steps. First, remote sensing data were classified to map crop types. Second, landscape metrics were used to examine the spatial patterns of agricultural land cover concerning urbanisation levels. Finally, unsupervised clustering was applied to categorise agricultural landscape types along the urban–rural interface. The workflow was tested using WorldView-3 satellite data in Bengaluru, India. It identified four major herbaceous crop types (millet, maize, pulses, and cash crops) and woody plantations as agricultural land cover. An analysis revealed that agricultural land cover increased from urban to rural areas, with diverse patterns in transition zones. The cluster analysis characterised four agricultural landscapes. The findings imply that changes in an agricultural landscape along an urban–rural gradient are not linear. The newly developed integrated workflow empowers stakeholders to make informed and well-reasoned decisions, and it can be periodically implemented to maintain the ongoing monitoring of urbanisation’s effect on food systems.